WHY INPATIENT VISITS DECREASED DURING THE PANDEMIC? CASE STUDY IN HOSPITAL X, MALANG REGENCY - Lukito, Anggun Agatha Cristy; Widyaningrum, Kurnia (Jurnal Kedokteran Brawijaya)
ABSTRACTCovid-19, designated as a National disaster in Indonesia, has an impact on reducing the number of non-Covid-19 inpatient visits in almost all hospitals. Hospital X also underwent a decrease in inpatient visits, resulting in a decrease in the Bed Occupancy Rate (BOR) by 35,5%. The study aimed to identify the factors causing the decrease in the number of inpatients at Hospital X from April to July. This study used a qualitative descriptive approach with Focus Group Discussion (FGD) data collection techniques analyzed using Fishbone Diagram combined with 5 WHYs. The subjects were determined based on purposive sampling, namely 8 respondents consisting of the head of the inpatient room, the coordinator of the inpatient room, the outpatient coordinator, head of public relations and marketing unit, and the coordinator of the patient registration office. Through the Fishbone Diagram, there found several root cause themes covering 4 aspects, namely the Human aspect, the Method aspect, the Mother Nature or the Environment aspectÂ  and the Market aspect as the cause of the decrease in the number of hospitalized patients atÂ  Hospital X during the Covid-19 pandemic.Â